If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(7 + -2x) = 39 (7 * -3 + -2x * -3) = 39 (-21 + 6x) = 39 Solving -21 + 6x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 6x = 39 + 21 Combine like terms: -21 + 21 = 0 0 + 6x = 39 + 21 6x = 39 + 21 Combine like terms: 39 + 21 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| -7(-3+5x)=21 | | 5(-2-4x)=70 | | 0=t^3+t^2-10t+8 | | 7(6x-2)=-476 | | 5(-8+7x)=-40 | | -5(-2x+4)=90 | | -5(1x+7)=-20 | | 2(1+1x)=24 | | 19/20*32 | | -5(2+7x)=-10 | | 3.14*4*1= | | 32*19/20 | | 15a^2+7ab-2b^2=0 | | 3x-3=-38-2x | | 4(3+3c)=56 | | 6(x+1)(x+1)-14=0 | | 10(x-2)=-2+40 | | 10+4x=7x+4 | | -12=-2x+3 | | 8+x=-4x-32 | | (5/7)=(x/21) | | 4y=-2x-1 | | 0.009/9 | | x+4=76-5x | | 33-x=33 | | 0.09/18 | | 7x-3=3x+41 | | 11(-5+4)= | | -y-7=-12 | | 576+100=x | | 2+6x+6x=26 | | Log(2)523=x |